Daratumumab, lenalidomide, and dexamethasone for multiple myeloma - Dimopoulos, Meletios A.; Goldschmidt, Hartmut (The New England journal of medicine, 2016)
The addition of daratumumab to lenalidomide and dexamethasone resulted in superior response rate and progression-free survival, as compared with lenalidomide and dexamethasone alone, at a cost of more frequent neutropenia and infusion reactions.